Introduction of a neutral shoe to assess reference values for dynamic pedobarography - Kluger, Anna Katharina; Carl, Hans-Dieter; Jendrissek, Andreas; Swoboda, Bernd; Hotfiel, Thilo (Biomedizinische Technik, 2014)
The aim of our study was to introduce a so-called "neutral shoe" as a tool to assess reference values for dynamic pedobarographic investigations.Twelve healthy volunteers were asked to participate. During the first trial the participants were asked to walk with a neutral shoe (Breidbach, Germany). The second trial was performed with the running shoe "Faas 500" (Puma SE, Germany). Peak plantar pressure values were analyzed from nine foot regions using the Pedar® X system (Novel Inc., Munich, Germany).The mean peak pressure reduction for the total foot was 36% under the left (non-preferred) foot and 32% for the right (preferred) foot. A statistically significant reduction of peak pressure was observed for eight regions, from a mean 14% peak pressure reduction under the right metatarsal head 1 up to a 41% peak pressure reduction under the right big toe.The neutral shoe is a feasible tool to assess reference values for dynamic pedobarography. Such a reference tool may help to standardise several steps in the development and construction of shoes and orthotic devices.
EVALuna2:10897